Transforming Forms and Methods of Learning: Challenges and Opportunities - L. S. Babynina (Plekhanov Russian University of Economics, 2021)
The article examines the state of forms, methods and technologies of education during the period of introduced restrictive measures caused by coronavirus infection. For a generalized assessment of the current situation in the educational environment, the authors used international and Russian studies during 2020 (UNESCO global monitoring of education, reports of the International Talent Development Association, Analytical report of the Ministry of Science and Higher Education, survey results of the RAEX rating agency), scientific articles and their own developments obtained within the framework of research activities in the preparation of management personnel in the framework of the Federal Presidential Program. The problems of the implementation of training that have arisen as a result of the transition to distance learning, both on the part of teachers and on the part of students, are considered. The article analyzes the reaction of students to the preservation of distance learning during the transition to the full-time format. The development of information and communication technologies allows the use of asynchronous, synchronous and blended learning. The authors identified three main problems faced by educational programs. They are associated with the forms and methods of teaching, technical and information support of the educational process, the ratio of distance learning, the transformation of digital and personal competencies of professors. It is noted that forms of blended and distance learning are becoming more and more attractive. To adapt educational programs of all levels to current trends and student needs, the authors propose to use the technology of "flipped classroom" (Flipped Classroom) or "flipped learning" (Flipped Learning).